The study of the anti fungal effect of flax seed in vitro (Comparative study) - Mustafa Al-Ahmad, Basma Ezzat; Qaralleh, Haitham; Abdul Azi, Ahmad Hafiz; Amdan, Mohd Hilmi (2012)

(untitled)
Flaxseed (Linum usitatissimum) or linseed is a natural product that has been found to have anticandidal, anticancer, antibacterial and antiviral properties. Thus, the extraction of its oil has become an important industrial process. The aim of this research is to investigate the anti-candidal activity of flaxseed extract in vitro. Disc diffusion method was performed and the zones of inhibition around the disc within each petri dish were measured after 48 hours of incubation period. Two different extracts including oil-based flaxseed extract and water-based flaxseed extract were evaluated using disc diffusion method at different volume per disc (5µl, 10µl and 15µ) and compared with nystatin. The result shows that the oil-based flaxseed extract shows no antifungal activity regardless of the quantity used. But, water-based flaxseed extract presents anti-candidal activity. The higher the quantity of water-based flaxseed extract used, the bigger the zone of inhibition recorded. Thus, water-based flaxseed extract might be promising if used as a mouthwash to reduce fungal infection in oral cavity and the incidence of side effect that may occur with some synthetic product.